FAKTOR – FAKTOR PENGEMBANGAN KARIR BERBASIS KOMPETENSI TERHADAP KINERJA KARYAWAN DI PT. PG RAJAWALI II UNIT PG KARANGSUWUNG - Asep Gunawan; Shinta Rosaindah Utami (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2014)
A company in carrying out its activities are in need of the factors of production such as raw materials, machinery, and human resources. These factors must be carried out effectively and efficiently in order to achieve the goals set by the company. Labor or employee plays an important role in a company, because the company will not be developed and supported by the ability to grow without labor or employee even if the company has a complete infrastructure and sophisticated, because of all the activities undertaken by a firm depends on factors man, from planning, implementation, control The objectives in this study was to determine the influence of factors - competency -based career development factors affect the performance of employees at PT. PG Rajawali II Unit Karangsuwung. The method used in this study is a survey method. The conclusions of this study is that the variable t for career development factor of 7,454. So the value of the variable t is greater than t table (7,454 > 1,680), so that in partial career development factors have an influence on the performance of the employee, that the competence of the variable t for 2808. So the value of the variable t is greater than t table (2,808 > 1,680), so that in partial competencies have an influence on employee performance and based on the results obtained Fcount 32 504. While the F table with degrees of freedom k and v1 = v2 = n - k - 1 and with a = 0.05) obtained Ftable 2,790. aconfidence level of 95 % (Thus F value is greater than the value of F table ( 32 504 > 2,790 ) . Thus it can be said that the variable factor of career development and competency have influence with , meaning that the two variables are always influencing the performance of employees at PT. PG Rajawali II Unit Karangsuwung Keyword : competency, career, PT. PG Rajawali